1999
DOI: 10.1002/(sici)1096-9101(1999)24:2<133::aid-lsm9>3.3.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Use of an agent to reduce scattering in skin

Abstract: Background and Objective:A method to increase light transport deeply into target areas of tissue would enhance both therapeutic and diagnostic laser applications. The effects of a hyperosmotic agent on the scattering properties of rat and hamster skin were investigated. Study Design/Materials and Methods: A hyperosmotic agent, glycerol, was applied in vitro and in vivo to rat and hamster skin to assess the changes in tissue optical properties. Changes in the reduced scattering coefficient after application of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
98
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(101 citation statements)
references
References 10 publications
(8 reference statements)
2
98
0
1
Order By: Relevance
“…Topically applied hyperosmotic agents have been used as optical clearing materials in previous studies utilizing both optical coherence tomography (OCT; (2,2224)) and low-level emitted light (bioluminescence) imaging (25). Although it is possible that OCT may be more sensitive to alterations of light penetration induced by glycerol than NIR imaging, it is also possible that dehydration from air exposure during the procedure is creating a situation analogous to our non-hydrated ex vivo samples, and that glycerol is acting to change the hydration status of the tissue (2,4,6,26).…”
Section: Discussionmentioning
confidence: 99%
“…Topically applied hyperosmotic agents have been used as optical clearing materials in previous studies utilizing both optical coherence tomography (OCT; (2,2224)) and low-level emitted light (bioluminescence) imaging (25). Although it is possible that OCT may be more sensitive to alterations of light penetration induced by glycerol than NIR imaging, it is also possible that dehydration from air exposure during the procedure is creating a situation analogous to our non-hydrated ex vivo samples, and that glycerol is acting to change the hydration status of the tissue (2,4,6,26).…”
Section: Discussionmentioning
confidence: 99%
“…Since Vargas et al [5] first reported optical tissue clearing by glycerol, HCAs have been frequently utilized as an effective method to reduce light scattering of tissue and, therefore, improve optical tissue clearing. HCAs have been shown to induce optical tissue clearing by skin dehydration and collagen dissociation or a combination thereof [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…912 Such resolution recovery schemes can be further enhanced through locally incorporating optical clearing chemical agents 1316 or producing mechanical compression by reducing refractive index mismatch between compact proteins to improve optical transmission. 17 These innovations, however, are unable to minimize the background signals coming from tissue auto-fluorescence, and often sacrifice total signal for resolution improvement.…”
Section: Introductionmentioning
confidence: 99%